2002
DOI: 10.1002/mds.10243
|View full text |Cite
|
Sign up to set email alerts
|

Dopa‐responsive parkinsonism phenotype of spinocerebellar ataxia type 2

Abstract: We report on 2 brothers, Patients 1 and 2, who presented with a similar clinical syndrome consisting of resting tumor, bradykinesia, rigidity, and dysarthria at the ages of 40 and 43 years, respectively. An excellent response to levodopa therapy was observed throughout the disease course. No gait or limb ataxia, slow saccades, or decreased tendon reflexes were detected, but unsteadiness of gait with propulsion developed recently in Patient 1 approximately 25 years after disease onset. Magnetic resonance imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 26 publications
2
46
1
Order By: Relevance
“…12). The sign of dopamine-responsive just has been seen in some Chinese families 13,14 and some white families. 15,16 We described here a large family from Hubei, China, that showed primarily autosomal dominant inheritance of parkinsonism symptoms acrossing four generations.…”
Section: Introductionmentioning
confidence: 93%
“…12). The sign of dopamine-responsive just has been seen in some Chinese families 13,14 and some white families. 15,16 We described here a large family from Hubei, China, that showed primarily autosomal dominant inheritance of parkinsonism symptoms acrossing four generations.…”
Section: Introductionmentioning
confidence: 93%
“…We observed down-regulation of Gabarapl2, a protein involved in vesicle transport and axonal elongation in mammalian neurons [26] and ataxin-2, a protein associated with spinocerebellar ataxia type 2; it is of note that a subset of patients with parkinsonian phenotype responded to dopamine treatment suggesting a link between ataxin-2 and dopamine [39]. On the other hand, previous studies have shown both decreased dopaminergic activity and increase in DOPAC:DA ratio in the hypothalamus of mice injected with mammary tumor cells and lymphoma cells, respectively [11,40].…”
Section: Discussionmentioning
confidence: 69%
“…One patient was diagnosed as progressive supranuclear palsy because of the presence of bradykinesia, lack of response to L‐Dopa, prominent vertical gaze palsy but not ataxia signs. Several other families with parkinsonian phenotype have been described since then 90, 91, 92, 93, 94. Number of CAG repeats was <40 repeats and the sequence was interrupted by CAA when explored.…”
Section: Atxn2 and Parkinsonismmentioning
confidence: 99%
“…It is not known the prevalence of asymptomatic cerebellar atrophy in parkinsonian patients. SCA2 expansions explained 0–2% of familial parkinsonism in Caucasian94, 95, 96 and up to 10% in Asian population 92, 93…”
Section: Atxn2 and Parkinsonismmentioning
confidence: 99%